Sectoral and regional impacts of the European Carbon Market in Portugal - Alves, M. R.; Rodríguez, M.; Roseta-Palma, C. (Energy Policy, 2011)
Across Europe, CO(2) emission allowances represent one of the main policy instruments to comply with the goals of the Kyoto Protocol. In this paper we use microdata to address two issues regarding the impact of the European Carbon Market (EU ETS). First, we analyze the sectoral effects of the EU ETS in Portugal. The goal is to study the distributive consequences of imbalances, with the novelty of taking into account firm financial data to put values into context. We show that a large majority of installations in most sectors had surpluses and the opportunity to raise remarkable revenues in some cases. We also look at the regional impact, since the pre-existing specialization of different regions in the production of different goods and services might lead to an uneven economic impact of the allowance market. In particular, Portuguese data indicate a distribution of revenue from low income to high income regions, or rather, between installations located in those regions. We focus on the first phase of the EU ETS, using data for each one of the 244 Portuguese installations in the market as well as financial data for 80% of these installations, although we also present data for 2008 and 2009.